AGORA VIII - jobrotation : Thessaloniki, 20 - 21 March 2000 - (:unkn) unknown (Office for Official Publications of European Communities, 2002)
"The term 'jobrotation' has a specific meaning: it designates a measure, a technique and a sophisticated tool for investing in human capital. Jobration initiates transference between work and training. The idea is, firstly, to makre it possible for employees to leave their jobs temporarily in order to be trained, without this causing any major break in production. Secondly, somebody from outside the firm replaces the employee who is receiving training, in such a way that the number of employees in the firm remains unchanged and the replacement workers are operational immediately. Thirdly, when employees return from their training, their enterprise benefits from their increased efficiency; at the same time, their replacements have acquired a new skill. Finally, the latter may have acquired an established position in the enterprise, or alternatively can replace another employee who is in turn going away for training, and so on." (Herausgeber, BIBB-Doku)
Keywords: G 1.2.2.3 Beschäftigungsformen; G 2.5.4 Qualifizierungs- & Ausbildungskonzepte; I 2.2.1 Westeuropa; I 2.1 Deutschland; I 2.1.2.9 Bremen; I 2.1.2.6 Nordrhein-Westfalen; Jobrotation; Weiterbildungsförderung; Arbeitsloser; Qualifizierung; Dänemark; Frankreich; Bundesrepublik Deutschland; Bremen; Nordrhein-Westfalen